ANALISIS BREAK-EVEN POINT SEBAGAI ALAT PERENCANAAN PENJUALAN DAN LABA TERHADAP USAHA MIKRO DI AMBON : (Studi Pada Usaha Mikro Minuman Boba Kedai Tosca OSM Kota Ambon) - J. VONNY LITAMAHUPUTTY; JULIE TH. PELAMONIA; TELLY NANLOHY (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The purpose of this study is to identify Break-Even Point (BEP) to create a seles and company profit plan at Tosca OSM Shop in Ambon as a boba beverage microenterprise. This study is done by interview and direct observation research. The data will be arranged depends on research needs and processed in several steps : calculating total sales in month, cost, contribution margin ratio, break-even point, sales and profit plan, and margin of safety. The result showed that break-even point to June 2022 in the amounts of sales Rp. 2.460.812,662 or 117 unit of products. In calculating the sales planning using the least square method on July 2022 were obtained at Rp 11.536.000 or 549 unit of products. The profit planning were obtained at Rp. 5.966.000 and margin of safety 78,67%. This shows that the Tosca OSM Shop as a boba beverage microenterprise can sell more than break-even point and has a high level of safety, so it is far from the losses that may be suffered.